2012
DOI: 10.1109/tasl.2011.2162322
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Reranking for Spoken Language Understanding

Abstract: Abstract-Spoken Language Understanding (SLU) is concerned with the extraction of meaning structures from spoken utterances. Recent computational approaches to SLU, e.g. Conditional Random Fields (CRF), optimize local models by encoding several features, mainly based on simple n-grams. In contrast, recent works have shown that the accuracy of CRF can be significantly improved by modeling long-distance dependency features. In this paper, we propose novel approaches to encode all possible dependencies between fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Conditional Random Fields (Lafferty et al, 2001) have been applied (e.g. Wang and Acero (2006a;Dinarelli et al (2012)); He and Young (2005) present an approach based on Hidden Markos Models. However, evaluations have shown that even in case of applying machine learning techniques or probabilistic models, semantic parsing of ASR transcriptions is affected by much more errors compared to parsing of correct transcriptions (De Mori, 2011).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Conditional Random Fields (Lafferty et al, 2001) have been applied (e.g. Wang and Acero (2006a;Dinarelli et al (2012)); He and Young (2005) present an approach based on Hidden Markos Models. However, evaluations have shown that even in case of applying machine learning techniques or probabilistic models, semantic parsing of ASR transcriptions is affected by much more errors compared to parsing of correct transcriptions (De Mori, 2011).…”
Section: Background and Related Workmentioning
confidence: 99%
“…However, such classification is not completely aligned to our purpose, since our goal is to select the best (i.e., the most correct) DT from k candidate DTs; i.e., a ranking task. We adopt a preference reranking technique as described in Dinarelli et al, 2011).…”
Section: Kernels For Reranking Discourse Treesmentioning
confidence: 99%
“…However, their model does not con- sider long range dependencies between DT constituents, which are encoded by our kernels. Regarding the latter, our work is surely inspired by (Collins and Duffy, 2002), which uses TK for syntactic parsing reranking or in general discriminative reranking, e.g., (Collins and Koo, 2005;Charniak and Johnson, 2005;Dinarelli et al, 2011). However, such excellent studies do not regard discourse parsing, and in absolute they achieved lower improvements than our methods.…”
Section: Related Workmentioning
confidence: 99%
“…Discriminative re-ranking in other domains. Discriminative re-ranking of multiple solutions is a dominant paradigm in domains like speech [9,10] and natural language processing [8,25]. In fact, the title of this paper is a reference to such speech & NLP papers.…”
Section: Related Workmentioning
confidence: 99%